CONCEPTUALIZACIÓN, CARACTERIZACIÓN Y DECONSTRUCCIÓN DEL TÉRMINO NAVE EN LA ARQUEOLOGÍA: UN ACERCAMIENTO A LOS ESPACIOS P-02 Y P-03 DEL SITIO ARQUEOLÓGICO NUEVO CORINTIO (L-72NC) - Castillo Poveda, Manuel (2015)
This article delves into the issue of language and reality, specifically in the allocation and use of terms outside the spatial or temporal environment of the researcher societies. Archeology in the nomination process of a space must be based on evidence, which affect our assimilation and comparison with our reality. This implies the need to carry out an assimilation or conceptual , in order to generate a better understanding of each site investigation and avoiding conceptual loads wrong.